The Ptolemaic Guard Сavalry Regiment - Sekunda, Nicholas Victor (Anabasis. Studia Classica et Orientalia, 2012)
The guard cavalry regiment of the Ptolemaic army, at least in its earlier existence was composed of ethnic Macedonians. It is not known for sure what the title of this regiment was. It might have been ’The Cavalry about the Court’ (οἱ περὶ τὴν ἄυλὴν ἱππεῖς), but this is uncertain. At the battle of Raphia in 217 BC the regiment numbered about 700 men. It was organized into squadrons (ilai) of which the elite squadron was entitled ’the royal squadron’ (ἥ βασιλικὴ ἴλη). The regiment was formed of cleruchs. The soldiers of this regiment were distinguished by their saffron-yellow cloaks with sea-purple borders, as were their predecessors in the Companion cavalry regiment under Alexander. It was a heavy cavalry regiment, wearing cuirasses and helmets, and, in its later stages shields. At the end of the fourth century the helmets were of the Boeotian type, but later on these at first replaced by a type of comb-crested close helmet.